2015
DOI: 10.1007/s00266-015-0532-6
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ Aesthetic Concerns After Horizontally Placed Abdominal Free Flap Breast Reconstruction

Abstract: This journal requires that authors assign a level of evidence to each article. For a full description of these Evidence-Based Medicine ratings, please refer to the Table of Contents or the online Instructions to Authors www.springer.com/00266 .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…This may augment the already problematic lateral subunit of the chest in addition to increasing axillary soft tissue excess and disrupting the natural lateral breast contour. Following free tissue transfer breast reconstruction from the abdominal donor site, the most common revision procedures include abdominal scar improvements, liposuction of the transferred flap, and fat grafting of the reconstructed breast [3]. In their review of 150 patients with abdominal free flaps for breast reconstruction, Kim et al found that 18.7% of patients required liposuction of the lateral breast and 20% received fat grafting of the superomedial pole [3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may augment the already problematic lateral subunit of the chest in addition to increasing axillary soft tissue excess and disrupting the natural lateral breast contour. Following free tissue transfer breast reconstruction from the abdominal donor site, the most common revision procedures include abdominal scar improvements, liposuction of the transferred flap, and fat grafting of the reconstructed breast [3]. In their review of 150 patients with abdominal free flaps for breast reconstruction, Kim et al found that 18.7% of patients required liposuction of the lateral breast and 20% received fat grafting of the superomedial pole [3].…”
Section: Discussionmentioning
confidence: 99%
“…Large volume suctioning is associated with an increased risk of fat necrosis [5]. The central-lateral and lower-lateral breast are most common for liposuction, whereas fat grafting is typically employed for the improvement of the upper-medial and upper-central breast [3]. Dermatolipectomy is typically performed to remove excess lateral chest or breast soft tissues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various reconstructive options are now available, including autologous tissue-based and prosthesis-based techniques. Autologous immediate reconstruction can usually provide esthetic, natural breasts with acceptable donor site morbidities in properly selected patients [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who have undergone abdominal free flap breast reconstruction usually have dog-ear deformities on both sides of the abdominal scar. After the abdominal free flap breast reconstruction, the most common secondary procedure is dog-ear correction of both flanks [3].…”
Section: Introductionmentioning
confidence: 99%